Cover Picture: Enantioselective Addition of a 2‐Alkoxycarbonyl‐1, 3‐dithiane to Imines Catalyzed by a Bis(guanidino)iminophosphorane Organosuperbase (Angew. Chem. Int. Ed. 52/2015). Issue 52 (4th December 2015) - Kondoh, Azusa; Oishi, Masafumi; Takeda, Tadahiro; Terada, Masahiro
Abstract : A chiral bis(guanidino) iminophosphorane catalyzes enantioselective addition reactions of a 1, 3‐dithiane derivative, which possesses a less‐acidic proton, as a pronucleophile. As demonstrated by M. Terada et al. in their Communication on page 15836 ff., the chiral uncharged organosuperbase facilitates the addition of benzylcarbonyl‐1, 3‐dithiane to aromatic N ‐Boc‐protected imines to provide optically active α‐amino‐1, 3‐dithiane derivatives.